A checklist of natural enemies of Diaphorina citri Kuwayama (Hemiptera: Liviidae) in the department of Valle del Cauca, Colombia and the world. - Kondo, Takumasa; González F., Guillermo; Tauber, Catherine; Guzmán Sarmiento, Yoan Camilo; Vinasco Mondragon, Andrés Felipe; Forero, Dimitri (Journal of World Insect Systematics, 2025)
In recent years, populations of the Asian citrus psyllid, Diaphorina citri Kuwayama (Hemiptera: Liviidae), have increased in rural citrus orchards and urban backyard gardens. In order to fi nd biological control options for D. citri, a search for natural enemies was conducted in the department of Valle del Cauca, Colombia. The collections were carried out in citrus orchards in rural areas and house gardens and street trees in urban areas. Natural enemies were collected from D. citri found on Citrus spp. and Murraya paniculata (L.) Jack (Rutaceae). A total of 16 species of natural enemies of D. citri distributed in six families in fi ve orders are reported from Colombia. Herein we provide an updated list of 95 species of arthropod (arachnids and insects) natural enemies of D. citri distributed in nine orders and 23 families recorded worldwide.